(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The study aims to describe the clinical and paraclinical characteristics and evaluate the results of microdiscectomy in patients with lumbosacral disc herniation with fragmented fragments. Research subjects and methods: Retrospective description and analysis of a series of cases. Cases undergoing microsurgery to remove lumbar disc herniation with fragmented fragments at the Department of Neurosurgery, Nguyen Tri Phuong Hospital from October 2019 to June 2022. Patients were evaluated for clinical symptoms and imaging before surgery; assess the level of symptom improvement after surgery according to the VAS and Macnab scales. Results: There were 37 cases, including 21 men and 16 women, the youngest 26 years old, the oldest 76 years old, who underwent microsurgery to remove the herniated nucleus pulposus with loose fragments. The level of nerve root pain according to the VAS scale at the time before surgery and immediately after surgery 24 hours was 8.11 ± 0.90 points and 2.30 ± 1.35 points, respectively. At 3 months after surgery, very good results accounted for 62.2% and good results accounted for 37.8%. Recorded 1 case of dural tear that was treated during surgery. No other complications were noted at 3 months after surgery. Conclusion: Microsurgery to remove the nucleus pulposus on patients with lumbar disc herniation with separate fragments achieved good results with few complications.